Long-term effects of SARS-CoV-2 infection and vaccination in a population-based pediatric cohort - Jakob Höppner; Christoph Maier; Anne Schlegtendal; Anna Hoffmann; Astrid Petersmann; Thomas Lücke; Nicole Toepfner; Folke Brinkmann (Scientific Reports)
Abstract During the omicron wave of the COVID-19 pandemic and with SARS-CoV-2 vaccines becoming available, seroprevalence rates rose in children and adolescents. This study investigated the impact of both SARS-CoV-2 infections and vaccinations on the incidence of acute and prolonged symptoms in real-world conditions during the transition from the pandemic to the endemic phase. Participants from a pediatric population based seroprevalence study (CorKID study) were followed up at least two and for almost four years by survey of health status features and symptoms suggestive of post-COVID syndrome (PCS). In a subgroup (n = 259) SARS-CoV-2 antibody serology was further investigated. 789 participants of the original CorKID study cohort (n = 2.121; 37.2%) were included. 67.9% reported at least one SARS-CoV2 infection. 46.6% had received one or more SARS-CoV-2 vaccinations. In the vast majority of serologically tested participants antibodies again SARS-CoV-2 spike (98.9%) or nucleocapsid (93.3%) antigen were detected following infection and/or vaccination. At least 30% experienced one unrecognized SARS-CoV-2 infection. The overall health status was comparable between children, irrespective of SARS-CoV-2 infections and similar to pre-pandemic assessment. However, a subset of young adolescents exhibited a decline in physical performance compared to pre-pandemic conditions. After infection, PCS-like symptoms persisted in 7% of the respondents for more than three months and up to four years. SARS-CoV-2 vaccinated participants (47%) reported 12% less acute flu-like infections other than SARS-CoV-2. Nearly all participants developed SARS-CoV-2 antibodies in this longitudinal study through either vaccination or infection during the Omicron wave. About 7% of participants suffered from PCS symptoms, predominately fatigue and exhaustion. Furthermore, participants who received vaccinations against SARS-CoV-2 reported a lower frequency of acute infections during follow-up.